Robert Bell’s Professorship at Queen’s University, 1864–1868 - Brookes, Ian (Geoscience Canada, 2011)
SUMMARY Robert Bell (1841–1917) taught at Queen’s College (now University) at Kingston, Ontario from 1864 to 1868, having previously served seven years as assistant at the Geological Survey of Canada (GSC). From Queen’s, he rejoined the GSC, serving until he was superannuated in 1908, elevated contentiously to ’Acting’ Director from 1901-1906. He was 23 years of age when he took up the Queen’s position, but was already recognized among the small local geological community as an authority on the Glacial Period. His time at Queen’s was not happy – his predecessor had left under a cloud, there was opposition to his succession to the post, faculty opponents coopted students, who harassed Bell with classroom rowdyism, all of which he met with insistence on the Administration’s support and regularization of his appointed ‘interim’ status and remuneration. At Queen’s he lost ground professionally, particularly through his dubious involvement in assessing goldmining properties in Nova Scotia (1868), in which a group of Kingston Town and Gown ‘worthies’ had invested development capital. However, we can add that gains were also made through several positive factors: i) his completion of the section on ‘Superficial Deposits’ for Sir William Logan’s Geology of Canada (1863); ii) membership in James Richardson’s GSC party to the Magdalen Islands and Newfoundland (1867); iii) his leadership of GSC field parties to Manitoulin Island (1865, 1866); and iv) visits to Scotland in 1864 and 1868, where he sat at the feet of several eminent scientists at the University of Edinburgh, and met the Glasgow family into which he would marry in 1873.